1987
DOI: 10.1002/jcp.1041330212
|View full text |Cite
|
Sign up to set email alerts
|

Growth of a human carcinoma (HEp3) in nude mice: Rapid and efficient metastasis

Abstract: Our aim was to identify conditions which would permit the development of spontaneous metastasis of a human tumor in nude mice in a rapid and predictable manner and to explore ways to quantitate metastasis. Using a human squamous carcinoma--HEp3--we determined that invasiveness and metastasis were influenced by the host. HEp3 cells grew very rapidly and without a significant lag period in Balb/c and NIH(S)-II nude mice kept in aseptic conditions; a much longer lag period was observed in NIH-Swiss mice kept in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 16 publications
4
23
0
Order By: Relevance
“…These results provide a functional link to our previous findings showing an increased S-phase fraction of T-HEp3 cells and a rapid G 0 -G 1 arrest of D-HEp3 cells, respectively, 48 hours after in vivo inoculation (10). These conclusions, reached through the study of a primary tumor, were also true for metastasis where we found ERK/Elk activation in growth-permissive metastatic sites at times when micrometastatic growth is known to begin (15). In both the primary and the metastatic sites, a proportion of the T-Elk cells had undetectable GFP levels, which suggested that the threshold of ERK signaling that is required to induce GFP is higher than that required to promote cell cycle progression, or indicated a more complete silencing of ERK signaling and induction of dormancy.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…These results provide a functional link to our previous findings showing an increased S-phase fraction of T-HEp3 cells and a rapid G 0 -G 1 arrest of D-HEp3 cells, respectively, 48 hours after in vivo inoculation (10). These conclusions, reached through the study of a primary tumor, were also true for metastasis where we found ERK/Elk activation in growth-permissive metastatic sites at times when micrometastatic growth is known to begin (15). In both the primary and the metastatic sites, a proportion of the T-Elk cells had undetectable GFP levels, which suggested that the threshold of ERK signaling that is required to induce GFP is higher than that required to promote cell cycle progression, or indicated a more complete silencing of ERK signaling and induction of dormancy.…”
Section: Discussionsupporting
confidence: 88%
“…6A). In the nude mouse, a permissive organ for HEp3 metastasis is the lung, in which we have shown that at the time of primary tumor removal 10% of mice have lung metastases and, 4 weeks later, 61% of the mice have lung metastases (15,19). In contrast, the liver and spleen are sites known not to harbor overt HEp3 metastases in nude mice.…”
Section: Monitoring Erk and P38 Signaling In Tumor Cells In Vivomentioning
confidence: 83%
See 1 more Smart Citation
“…Although several in vitro models have been described previously, in vivo working models for dormant and recurrent growth have yet to be developed. Recent attempts have characterized syngeneic head and neck squamous cell carcinoma cells (T-Hep and D-Hep) or a pair of breast cancer cell lines (D2.OR and D2A1 cells) that recapitulates dormant growth in vivo (13,(15)(16)(17). However, there is still no appropriate in vivo model that mimics dormancy and recurrence for prostate cancer, especially one that replicates the phenomenon of bone recurrence in patients.…”
mentioning
confidence: 99%
“…Human epidermoid carcinoma HEp3 (T-HEp3), 25 tumorigenic and metastatic in the chick embryo and in nude mice, 26,27 was serially transplanted on chorioallantoic membranes (CAMs) and used as a source of tumorigenic cells. T-HEp3, HEK-293 (human embryonic kidney) and the derived stably transfected cell lines were cultured in DMEM with 10% FBS.…”
Section: Peptide Synthesis and Purificationmentioning
confidence: 99%